Determinant factors of health financing among public and private sector in Malaysia - Mohd Ashhari, Zariyawati; Md Tahir, Hirnissa; M. S., Nurul Farhanim; Soh, Wei Ni (Canadian Center of Science and Education, 2021)
Health is a necessity for human well-being and productive. Hence, access to healthcare when needed is considered by many to be a basic human right. Therefore, it is important to invest in health financing to ensure access to healthcare for future needs, such as medical expenses. The current study aims to investigate the factors that influence employee spending on health financing in the public and private sectors in Malaysia. Further, we also examine whether the intention to spend on health financing differs between public and private sector employees. Multiple regression analysis and an independent-samples T-test were applied using SPSS to achieve this objective. Findings of this study reveal that employer and social influence factors influence the intention to spend on health financing in both sectors. Meanwhile, job factors only influence employees in the public sector to spend on health financing. We also found that the intention to spend on health financing differs between public and private sector employees.